IMPLEMENTASI SISTEM INFORMASI PERSEDIAAN BARANG DAGANG UD. CAHAYA ELEKTRONIK - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2020)
Computerized system is important in monitoring the sale and purchase transaction. If a computerized system is used, because with the computer there will be a detailed report data if the input data correctly, so there will be no mistake again. The problem also experienced by UD. Cahaya Elektronik that specializes in the sale. To overcome these problems, the authors designed a control system sales and purchases that have been computerized, where the system using Microsoft Access 2007 database for report generation and run on Microsoft Windows 7 operating system or a higher version of Windows. With this system, manually inputted data will be processed by the database management system better. With the computerized system, the UD. Cahaya Elektronik will gain some convenience gained from the system include minimizing the error in terms of inventory control. Systems also provide ease in viewing the merchandise inventory, printing sales invoices, card making supplies of goods, and report the inventory. Keywords: Implementation, Information Systems, Merchandise Inventory